Microsoft teams 365 and online learning: The student’s perception - Leony Sanga Lamsari Purba (Jurnal Pendidikan Kimia (JPKim), 2021)
study aims to determine the effectiveness of online learning using Microsoft Teams 365. The entire population in this study was used as a research sample, namely all students of the Chemistry Education study program, Indonesian Christian University, Jakarta. Perception data was collected using a questionnaire with dimensions of understanding the material, appearance and accessibility of Microsoft Teams 365. From the results of data processing, it was found that more than 50% of students' perceptions of Microsoft Teams 365 were good in all indicators of understanding the material and appearance. On the use dimension with connectivity and accessibility indicators more than 50% of students' perceptions of the Microsoft 365 team are good, but on the quota-saving indicator 42% of students do not agree. Keywords: Microsoft teams, E-learning, Cemistry